Xuzhou Construction Machinery Group - Zheng, Xiaoming, active 2020; Zhao, Ziqian, active 2020; Guo, Yirong (London : Tsinghua University School of Economics and Management, 2020)
XCMG was a leading construction machinery manufacturer in China, competing in a highly competitive international market. This case describes XCMG's chairperson Wang Min's role in the company over several stages of development. In the late 1990's, he eliminated corruption among XCMG's management personnel, pushed for the consolidation of dozens of unprofitable affiliates, and led the group through a period of turmoil into high growth. In the early 2000's, he actively sought a capital injection to power XCMG's next stage of growth. In a period of market downturn after 2011, his determination to stay in the construction machinery business reassured employees at XCMG and boosted their morale. In the following years, he steered the company towards two new strategic goals-internationalization and digitalization.This case provides students with an example of a long-serving leader who has exerted significant personal influence over his organization, and has played different roles in the highs and lows of the company. It is suitable for a discussion of how a leader's vision and values can impact the strategic goals of the company and its corporate values. The open-ended topic of this case is-What should a company do to pass on its corporate culture and spirit to the next generation of leaders, especially when the company is developing rapidly or experiencing dramatic changes in its business environment?
Originally Published in Zheng, X., Zhao, Z., & Guo, Y. (2020). Xuzhou Construction Machinery Group. 9-819-341. Beijing: Tsinghua SEM China Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Corporate culture -- Case studies; Leadership -- Case studies